The formulation of welfare state: the perspective of Maqāṣid al-Sharī‘ah - Elviandari Elviandari; Farkhani Farkhani; Khudzaifah Dimyati; Absori Absori (Indonesian Journal of Islam and Muslim Societies, 2018)
This paper examines empirical facts of market failure and government failure toimprove people’s welfare; capitalism and neo-liberalism do not provide a spacefor states to implement policies for social justice. With regard to the failure of thewelfare state to bring the citizen to fair welfare, this paper offers the formulationof a welfare state based on Maqas}id Al-Shari‘ah. This study employs Maqas}id Al-Shari‘ah developed by Imam Al-Juwaini, Izzu al-Din bin ‘Abd al-Salam, AbuIshaq al-Shatibi and Al-Tahir Ibn ‘Ashur as the methodological framework.It formulates welfare state of maqas}id al-shari‘ah, which is built through thefulfillment of the three levels of individual needs (citizens) (al-D}aruriyah, alhajiyyah and al-tahsiniyah; primary, secondary and suplementary rights), publicneeds (equal distribution; al-hajah al-‘ammah), protection or assurance (alismah),and law enforcement (al-fit}rah (order), equality (al-musawah), freedom(al-h}urriyah), magnanimity (al-samh}ah)). The morality-spirituality-religiosity andtranscendence principles develop the formulation. The maqas}id al-shari‘ahshould be the “soul” of every policies and rules or laws. The development ofthe formulation of welfare state based on Maqas}id al-Shari‘ah will build Islamicman/religious man (citizen), who is prosperous spiritually and materially.Artikel ini mengkaji kenyataan empiris mengenai kegagalan pasar(market failure) dan kegagalan negara (government failure) dalam meningkatkankesejahteraan rakyat, kapitalisme dan neo-liberalisme tidak memberikantempat bagi negara untuk melakukan kebijakan demi keadilansosial. Berdasarkan kegagalan negara kesejahteraan menghantarkanwarga negara menuju kesejahteraan yang berkeadilan maka tulisan inimenawarkan formulasi negara kesejahteraaan berdasarkan Maqas}id al-Shari‘ah. Kajian ini mempergunakan Maqas}id al-Shari‘ah sebagai kerangkametodologis yang dikembang oleh Imam Al-Juwaini, Izzu al-Din bin‘Abd al-Salam, Abu Ishaq al-Shatibi dan Al-Tahir Ibn ‘Ashur. Kajian inimemformulasikan negara kesejahteraan berdasarkan maqas}id al-shari‘ahyang dibangun melalui pemenuhan kebutuhan individu (warga negara)berdasarkan tingkatannya; al-D{aruriyah, al-h}ajiyyah dan al-tah}siniyah (hakprimer, sekunder dan suplementer), kebutuhan publik, (al-h}ujah al-‘as}mmah) terealisasi pendistribusian yang merata, adanya proteksi atau jaminan(al-is}mah) dan tegaknya hukum melalui, al-firah (ketertiban), equality(al-musawah) kesetaraan, freedom (al-h}uriyah) kebebesan, magnanimity (alsamh}ah) toleransi. Formulasi tersebut dibangun dengan landasan moral-spritual - religius dan transendental. Menjadikannya “roh” pada setiapkebutuhan dalam membuat kebijakan, peraturan-peraturan atau perundang-undangan. Dengan terwujdnya formulasi negara kesejahteraaanberdasarkan Maqas}id al-Shari‘ah akan melahirkan islamic man/manusiareligius/karakter (warga negara) yang beriman atau pribadi yang memilikikarakter, sejahtera secara batin (spritual) dan lahir (material).